Terapi kognitif perilaku untuk mengurangi gejala kecemasan - Muhammad Haikal (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Anxiety is a psychological disorder that can interfere with daily activities. Individuals who experience anxiety will develop cognitive distortions and maladaptive behavior. In general, anxiety is characterized by feelings of irritability, restlessness, difficulty sleeping, difficulty concentrating, and heart palpitations. The purpose of this study was to see whether Cognitive Behavioral Therapy could reduce anxiety symptoms. The subject is one person, female and 26 years old. The assessment methods used are clinical interviews, observation, graphic tests, thematic perception tests, Beck Anxiety Inventory, self-report, WHODAS 2.0, and Mental Status Exam. The therapy used to overcome social anxiety is Cognitive Behavioral Therapy with cognitive restructuring techniques and deep breathing relaxation techniques. Cognitive restructuring aims to replace negative thoughts with positive ones; while the relaxation technique aims to make the subject have the skills to control anxiety. The results of the therapy show that cognitive behavioral therapy can reduce anxiety symptoms.